Spontaneous Intracerebral Hemorrhage Occurring During Sleep: Clinical Characteristics and Risk Factors - Inamasu, Joji; Wakahara, Sota; Oshima, Takeo (Asian Journal of Neurosurgery, 2025)
Ischemic stroke occurring during sleep has been known as wake-up stroke, and many studies have been conducted on the subject. On the other hand, there have only been a few studies on spontaneous intracerebral hemorrhage (ICH) occurring during sleep. To clarify their clinical characteristics and possible risk factors, a single-center retrospective study was conducted on nontraumatic ICH patients admitted to our institution between 2012 and 2017.Demographics and outcomes were compared between 119 patients with ICH occurring during sleep (sleep group) and 401 patients with ICH occurring during the awake period (awake group). Multivariate regression analysis was conducted to identify risk factors. Furthermore, clinical presentation in those 119 patients was further classified into three categories (deficits, sudden headache, and failure to wake up), and their association to the outcomes was evaluated.Compared with the awake group, the frequency of chronic kidney disease (CKD) and diabetes mellitus were significantly higher in the sleep group. Multivariate regression analysis identified CKD as a risk factor for ICH occurring during sleep. The in-hospital mortality rate was significantly higher in the sleep group. Among the three classifications, failure to wake up was indicative of high mortality rate.The current results that ICH occurring during sleep was indicative of worse outcomes is compatible with prior studies. Poorly controlled nocturnal hypertension in patients with CKD and diabetes mellitus may be responsible for the higher incidence of ICH occurring sleep in those populations. The three classifications according to clinical presentation may be useful as a prognosticator.
Keywords: intracerebral hemorrhage; sleep; risk factor; chronic kidney disease; diabetes